Research to Practice Around the World. - Griffith, Robin; Lacina, Jan (Reading Teacher)
An introduction is presented in which discusses several articles in the issue on topics including the process of inquiry as the philosophy underpinning the New Zealand curriculum; students' learning and development; and computer programming.